Dans la bibliothèque de Des Esseintes : Flaubert et Mallarmé - Judit Maár (Flaubert: Revue Critique et Génétique)
Iconic hero of the famous decadent Joris-Karl Huysmans’s novel, A Rebours, Des Esseintes collects in his library a precious collection of ancient and contemporary works, made up of his favorite readings including the works of Flaubert and Mallarmé.In this study, we continue to walk in the footsteps of A Rebours’s protagonist to offer a comparative reading of the texts of its two revered authors. For Flaubert, our main corpus will be Madame Bovary, for Mallarmé, it will be the poem published in gratitude to Huysmans, Prose pour Des Esseintes. This choice may be surprising: why compare the novel traditionally – and possibly mistakenly – considered to be a first masterpiece of realism, and the poem taken for one of the most enigmatic texts of symbolism? It seems to us, and we will try to demonstrate it here, that Flaubert's novel proposes possible interpretations which justify the connection with the mysterious Mallarmé’s poem. After a brief introduction devoted to the relationships between Huysmans, Flaubert and Mallarmé, as well as the evocation of their works in A Rebours, we will develop the triple theme of the absence, the unreal and the silence, as it presents itself in Flaubert's novel and in Mallarmé's poem. The conclusion will allow us to reinscribe A Rebours in this same theme.